Model Pengembangan Antental Care Berbasis Android “My Ada” Pada Ibu Hamil - Erlin Puspita; Jusuf Kristianto; Yuniarti Yuniarti; Susilo Damarini; Elvi Destariyani (Syntax Corporation Indonesia, 2023)
during pregnancy within the specified time. Specifically, two in the first trimester, once in the second trimester, and three in the third trimester. Currently, ANC visits are conducted by midwives to monitor the development of the mother and fetus during pregnancy using the MCH handbook.. During the Covid-19 pandemic, an application is needed because the application can make it easier for pregnant women to see their health development. This study aimed to design an Android-based Antenatal Care (ANC) application model for pregnant women. The method used in this study is the development of the ANC model for pregnant women using Android, with the first stage of doing the design. At this stage, modeling and designing of media applications based on needs are carried out, the second stage is developing, then developing media that has been designed through the assessment of a team of experts, and the third stage of Implementation is testing the media that has been prepared to the user. Conclusion: The results of the study obtained four aspects in the Android-based My ADA application, namely functional suitability, usability, reliability, and performance efficiency, the results of the My ADA application development were very feasible to use. Suggestion: results of this study are used as alternative recommendations for increasing ANC visits.